Allergic Disorders in Africa and Africans: Is It Primarily a Priority? - Erasto Vitus Mbugi, PhD (World Allergy Organization Journal, 2010)
In Africa, the burden of some diseases has been a problem for centuries. The spectrum of African diseases includes allergies, infections, nutritional deficiencies, and natural disasters. Efforts made by scientists to search for possible means of disease control have been outstanding; however, in some infections, solutions are still out of reach. In disease control programs, it might be worth-while to pay attention to the most striking diseases than merely follow a holistic approach. This short review tackles the problems of allergy and allergens in Africa as compared with other disease burdens that may suggest the need for a more balanced approach based on priority. Keywords: allergy, allergens, Africa